Colonial Disparities in Higher Education: Explaining Racial Inequality for Māori Youth in Aotearoa New Zealand. Issue 1 (14th January 2022) - Mayeda, David; France, Alan; Pukepuke, Tepora; Cowie, Lucy; Chetty, Marilyn
Abstract : While recent research shows a gradual increase of young Māori in Higher Education it remains the case that inequality amongst the Indigenous population remains entrenched and institutionalised. This article explains how national governments in Aotearoa New Zealand have failed to address the colonial disparities and inequalities in the Higher Education system. In this process we will show, through the lens of historical privilege and institutional racism, how these processes continue to shape and frame both opportunities and experiences for Māori youth. The article will also highlight what strategies are needed if a more inclusive Higher Education system is to be developed that addresses the disparities that young Māori encounter.